2020
DOI: 10.1002/mrd.23330
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin preserves the primordial follicle pool during cisplatin treatment in vitro and in vivo

Abstract: Rapamycin has been proven to effectively inhibit the activation of primordial follicles while cisplatin-induced the loss of primordial follicles due to the overactivation of the primordial follicle stockpile. Whether rapamycin could inhibit the loss of primordial follicles induced by cisplatin is still unknown. The ovaries of neonatal Sprague Dawley rats were cultured in vitro in different doses of rapamycin (0.08, 0.16, and 0.32 μg/ml) and cisplatin (0.1, 0.4, and 0.8 μg/ml). The immature BALB/c mice were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 49 publications
(58 reference statements)
1
11
0
Order By: Relevance
“…Reduced p-Akt levels in follicles were also observed by immunohistochemistry in a recent in vitro study of ovine ovarian tissue cultured for 7 days in combination with epigallocatechin-3-gallate (EGCG), which has strong antioxidant and anti-apoptotic properties and activates the PI3K/PTEN/Akt pathway [ 65 ]. Our results are in agreement with the recent study by Xie et al (2020), showing that rapamycin inhibited the activation of primordial follicles of 4‐day‐old rat ovaries in vitro [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Reduced p-Akt levels in follicles were also observed by immunohistochemistry in a recent in vitro study of ovine ovarian tissue cultured for 7 days in combination with epigallocatechin-3-gallate (EGCG), which has strong antioxidant and anti-apoptotic properties and activates the PI3K/PTEN/Akt pathway [ 65 ]. Our results are in agreement with the recent study by Xie et al (2020), showing that rapamycin inhibited the activation of primordial follicles of 4‐day‐old rat ovaries in vitro [ 45 ].…”
Section: Discussionsupporting
confidence: 94%
“…Tsc2 can also be phosphorylated and inactivated by Akt, leading to activation of mTORC1 and phosphorylation of ribosomal protein S6 (rps6) [ 44 ]. Rapamycin, a specific mTOR inhibitor, is used as an immunosuppressant after organ transplantation and as a drug to prevent revascularization in coronary stents [ 45 ]. Inhibition of the activation of primordial follicles of 4‐day‐old rat ovaries in vitro was recently demonstrated using rapamycin [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of antitumoral drugs on ovarian function is the follicle-specific magnitude and is associated with the category of the drugs [ 12 ]. Some studies have declared that apoptosis occurred only in GCs of growing follicles, but not in PFs by TUNEL staining after treatment of cyclophosphamide or cisplatin [ 54 , 55 ]. Other results insist that TUNEL and/or γH2AX staining are positive in oocytes but not in the GCs of PFs [ 46 , 50 , 56 ].…”
Section: Impact Of Chemo- and Radio-therapy On Follicle Quantitymentioning
confidence: 99%
“…A large number of studies have already suggested treatment with a wide variety of different molecules to protect oocytes from chemotherapy-induced apoptosis. These studies range from hormonal treatment with gonadotropin-releasing hormone analogues or luteinizing hormone [152] to the use of sphingosine1-phosphate, dexrazoxane, resveratrol or mTORC inhibitors [153]. Some of these treatments have shown protective effects in mouse models while others, also used in human trials, are controversially discussed.…”
Section: Potential For Suppression Of Oocyte Death During Chemotherapymentioning
confidence: 99%